PENGEMBANGAN AGRIBISNIS PESANTREN (Studi Kasus di Pondok Pesantren Al-Ittifaq – Ciwidey Kabupaten Bandung) - Rahmawati, Dian; Setiawan, Iwan; Karyani, Tuti (Universitas Galuh, 2023)
The potential of Islamic boarding schools as one of the Islamic economic centers in Indonesia is important to continue to be empowered and developed, one of which is in the development of the agribusiness sector. Efforts to develop Islamic boarding schools have occurred sporadically in Indonesia, both independently and collaboratively. Agribusiness development is an approach to agricultural development that does not only cover agribusiness; but also includes production, distribution and marketing. The aims of this study were: (1) To find out the development of agribusiness in Islamic boarding schools (2) To know the patterns of horticultural agribusiness development in Islamic boarding schools (3) To know the collaboration or partnership of Islamic boarding schools (4) To analyze the determinants of Islamic boarding school agribusiness development. This research was conducted using qualitative methods with case study techniques. Data collection was carried out by in-depth interviews with two key informants and six supporting informants. The collected data were analyzed by ethical, emic and dialectical. The research was conducted for three months from October 2022 to January 2023. The results showed that agribusiness development at Al-Ittifaq Islamic Boarding School was carried out by forming business units and forming agribusiness development organizations. The pesantren agribusiness development pattern was formed by involving stakeholders including the pentahelix concept, namely academics, business, society, government and media. Partnerships are carried out with several traditional markets, modern markets and restaurants. In addition, partnerships are also carried out with financing institutions and research institutions. The determining factors include the role of the leader (Kiyai) and also the role of the santri.